PERAN ORANG TUA DALAM MEMINIMALKAN PERILAKU DISRUPTIF - Mudhar Mudhar (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Disruptive behavior is a form of behavior that many children do both verbally and non-verbally, such as raging, seeking attention, talking to his friends, and other annoying behavior. Disruptive behavior in early childhood often continues until later adulthood. Students with disruptive behavior raises concerns for families, schools, and communities. In particular, students with many performing annoying behaviors will experience more academic difficulties including. Many studies that explain the importance of parents in the process of child development, including in reducing the disruptive behavior of children. Although disruptive behavior in children is normal and normal, but if this issue is allowed to continue, it will have a greater negative impact. This paper will discuss the importance of parent-child relationships to minimize the disruptive behavior of children. In the process of interaction of children with parents there imitation process. The child's imitation of the behavior of one parent is a very possible manifestation of indirect influence in the family system. When his parents behaved brusquely to his son or to others, it is possible that his son will also imitate such things to others. In addition, family involvement is defined as the active involvement of family members, especially parents in the activities and behaviors of children at home and at school will be beneficial in their child's development, family involvement and parents will have an impact on the academic, psychological, social and positive behaviors others, including reducing disruptive behavior in children.